Coupling between Mercury and its nightside magnetosphere: Cross‐tail current sheet asymmetry and substorm current wedge formation. Issue 8 (19th August 2017) - Poh, Gangkai; Slavin, James A.; Jia, Xianzhe; Raines, Jim M.; Imber, Suzanne M.; Sun, Wei‐Jie; Gershman, Daniel J.; DiBraccio, Gina A.; Genestreti, Kevin J.; Smith, Andy W.
Abstract: We analyzed MErcury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENGER) magnetic field and plasma measurements taken during 319 crossings of Mercury's cross‐tail current sheet. We found that the measured B Z in the current sheet is higher on the dawnside than the duskside by a factor of ≈3 and the asymmetry decreases with downtail distance. This result is consistent with expectations based upon MHD stress balance. The magnetic fields threading the more stretched current sheet in the duskside have a higher plasma beta than those on the dawnside, where they are less stretched. This asymmetric behavior is confirmed by mean current sheet thickness being greatest on the dawnside. We propose that heavy planetary ion (e.g., Na + ) enhancements in the duskside current sheet provides the most likely explanation for the dawn‐dusk current sheet asymmetries. We also report the direct measurement of Mercury's substorm current wedge (SCW) formation and estimate the total current due to pileup of magnetic flux to be ≈11 kA. The conductance at the foot of the field lines required to close the SCW current is found to be ≈1.2 S, which is similar to earlier results derived from modeling of Mercury's Region 1 field‐aligned currents. Hence, Mercury's regolith is sufficiently conductive for the current to flow radially then across the surface of Mercury's highly conductive iron core. Mercury appears to be closely coupled to its nightside magnetosphere by mass loading of upward flowing heavy planetary ions and electrodynamically by field‐aligned currents that transfer momentum and energy to the nightside auroral oval crust and interior. Heavy planetary ion enhancements in Mercury's duskside current sheet provide explanation for cross‐tail asymmetries found in this study. The total current due to the pileup of magnetic flux and conductance required to close the SCW current is found to be ≈11 kA and 1.2 S. Mercury is coupled to magnetotail by mass loading of heavy ions and field‐aligned currents driven by reconnection‐related fast plasma flow. Key Points: Heavy planetary ion enhancements in Mercury's duskside current sheet provide explanation for cross‐tail asymmetries found in this study The total current due to the pileup of magnetic flux and conductance required to close the SCW current is found to be almost equal to 11 kA and 1.2 S Mercury is coupled to magnetotail by mass loading of heavy ions and field‐aligned currents driven by reconnection‐related fast plasma flow